Success Rates of Clomiphene Citrate and Recombinant Gonadotropin Cycles: A Single-Center Experience - Gurlek, Beril; Batioglu, Ali Sertac; Kanat-Pektas, Mine; Kale, Ibrahim; Onal, Ozgur; Yilmaz-Karakas, Nafiye (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: This aim of this study is to assess the ovulation induction cycles based on clomiphene citrate and gonadotropin administration and specify the factors associated with successful outcomes. Study Design: This is a prospective study of 631 patients who underwent 917 ovulation induction cycles. While clomiphene citrate was used in 680 cycles (74.2%) and recombinant follicle-stimulating hormone was administered in 237 cycles (25.8%). Results: A total of 153 pregnancies were achieved in 917 ovulation induction cycles, indicating a clinical pregnancy rate of 16.7%. The ovulation induction cycles which ended up with clinical pregnancy had a significantly lower frequency of smoking (p=0.005), shorter infertility duration (p=0.001), higher basal luteinizing hormone (p=0.021) and lower basal progesterone (p=0.008) than unsuccessful cycles. The clomiphene citrate cycles which ended up with clinical pregnancy had a significantly lower frequency of smoking (p=0.011), shorter infertility duration (p=0.001) and lower basal progesterone (p=0.013) than the unsuccessful cycles. The recombinant follicle-stimulating hormone cycles which ended up with clinical pregnancy had a significantly higher basal luteinizing hormone (p=0.008) than the unsuccessful cycles. Basal luteinizing hormone and progesterone concentrations could significantly distinguish the patients who were able to conceive in ovulation induction cycles (p=0.021 and p=0.008, respectively). Conclusions: Smoking, longer duration of infertility, and elevated basal progesterone are poor prognostic factors for clinical pregnancy in clomiphene citrate and recombinant follicle-stimulating hormone cycles.